Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1964
DOI: 10.1525/aa.1964.66.suppl_3.02a00050
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Interaction of Language, Topic, and Listener

Abstract: Sociolinguists study verbal behavior in terms of the relations between the setting, the participants, the topic, the functions of the interaction, the form, and the values held by the participants about each of these (Hymes 1962:25). Verbal behavior (talk and its equivalents) is the center of this definition, but of course a complete description of the system must include gestures or pictures when they are functional alternatives to linguistic signs. Verbal behavior is everywhere structured as a highly cohesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(56 citation statements)
references
References 25 publications
(8 reference statements)
2
50
0
4
Order By: Relevance
“…Early research in this area has identified the types of CS and the factors affecting it (e.g., Clyne, 1967;Ervin-Tripp, 1964;Fishman, 1965;Gumperz, 1964Gumperz, , 1967Gumperz & Hernández-Chavez, 1975). More specifically, CS varies according to the situation (situational code switching) and within a conversation (metaphorical code switching).…”
Section: Literature Review: Code Switching In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research in this area has identified the types of CS and the factors affecting it (e.g., Clyne, 1967;Ervin-Tripp, 1964;Fishman, 1965;Gumperz, 1964Gumperz, , 1967Gumperz & Hernández-Chavez, 1975). More specifically, CS varies according to the situation (situational code switching) and within a conversation (metaphorical code switching).…”
Section: Literature Review: Code Switching In Childrenmentioning
confidence: 99%
“…In this study, communicative competence refers to the speaker's knowledge of when to speak and when not to, and what to talk about with whom, when, where, and in what manner (Hymes, 1974). Based on previous research, we know that monolingual speakers have the capacity to switch between a variety of linguistic registers (e.g., Gumperz, 1967;Ervin-Tripp, 1964. Similarly, bilinguals also have these communicative registers that monolinguals have, but in addition they have two linguistic codes that they can alternate as a resource for sociolinguistic strategies during conversation.…”
Section: Introductionmentioning
confidence: 99%
“…Mingi keele kõnelejad on võimelised vahetama registreid (Gumperz 1967, Ervin-Tripp 1964. Samad võtted on olemas ka kakskeelsetel, kuid lisanduvad veel eri keeled.…”
Section: Eesti Rakenduslingvistika üHingu Aastaraamat 2 231249unclassified
“…Varasemates pragmaatilistes uurimustes on sõnastatus koodivahetuse tüübid ja seda mõjutavad faktorid (Ervin-Tripp 1964, Fishman 1965, Gumperz 1964, Clyne 1967, Gumperz, Hernández-Chavez 1975. Nimelt varieerub koodivahetus sõltuvalt situatsioonist ja vestluse eesmärgist.…”
Section: Eesti Rakenduslingvistika üHingu Aastaraamat 2 231249unclassified
“…While this is a study ofthe Japanese language spoken in AustralialNew Zealand, studies in other overseas varieties of Japanese provide us with invaluable data for comparison (other data include: Ervin-Tripp 1964Hiroshima, Yamaguchi, etc. )21 (Riga 1975;Kimura 1988: 30~32).…”
Section: Points To Notementioning
confidence: 99%